Hydroponic vegetable business strategy development in PT. XYZ - M Fariz Afif Hasibuan; Harianto Harianto; Lukman Mohammad Baga (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
PT XYZ is an agribusiness company. Currently, its potential is still not optimized. To support sustainable and competitive agricultural development and the sustainability of the industry in running a business, professional and efficient business plans and strategies are needed to achieve the business targets that have been set. This study aims to 1) analyze the business model run by PT XYZ, 2) analyze the internal and external conditions of PT XYZ, and 3) formulate an improvement plan for the business model of PT XYZ. The data used in this study are primary data and secondary data. Primary data was obtained through field observations, in-depth interviews with informants (purposive sampling), and distributing questionnaires. In contrast, secondary data came from various kinds of literature, both from books and the internet, regarding the results of data publications from relevant institutions and agencies relevant to the research. The method of analysis with research objectives are Business Model Canvas (BMC), SWOT (Strength, Weakness, Opportunity, and Threat) analysis, and qualitative and quantitative descriptive. The results of the Business Model (BMC) mapping at PT XYZ show that there is still a need for changes in business strategy because there are still potential customer segments to be developed. After using the SWOT analysis, there are several formulations of strategy development, namely a new alternative strategy focusing on several operational support components to reach broader consumers, integration between products and services, and a sound marketing management system.